1983
DOI: 10.1016/0002-8703(83)90006-6
|View full text |Cite
|
Sign up to set email alerts
|

Amiodarone pharmacokinetics

Abstract: The single-dose pharmacokinetics of amiodarone have been studied in volunteer subjects given 400 mg doses by the intravenous and oral routes. The data show the compound to have a very large volume of distribution, a low total clearance, and a long and variable terminal elimination half-life. In patients the terminal elimination half-life was on the order of 40 days, with a more rapid phase of elimination in the first few days following the withdrawal of therapy. The terminal elimination half-life of desethylam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
191
5
18

Year Published

1985
1985
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 402 publications
(234 citation statements)
references
References 18 publications
20
191
5
18
Order By: Relevance
“…Both amiodarone and its major metabolite desmethylamiodarone are measurable in plasma for at least nine months after cessation of amiodarone therapy. 24 We are unable to prove a definite cause and effect relationship between amiodarone therapy and the complications which we found; however, complications and mortality were significantly more frequent in patients taking amiodarone than in our control group of patients in whom one would expect a high incidence of complications and death.…”
Section: Discussioncontrasting
confidence: 74%
“…Both amiodarone and its major metabolite desmethylamiodarone are measurable in plasma for at least nine months after cessation of amiodarone therapy. 24 We are unable to prove a definite cause and effect relationship between amiodarone therapy and the complications which we found; however, complications and mortality were significantly more frequent in patients taking amiodarone than in our control group of patients in whom one would expect a high incidence of complications and death.…”
Section: Discussioncontrasting
confidence: 74%
“…These concentrations are within the therapeutic range defined in man (approximately 1.5-3.5mg litre-') (Holt et al, 1983).…”
Section: Treatment Regimessupporting
confidence: 60%
“…[16][17][18][19][20] Others found a clear concentration-related effect of amiodarone on QT-interval prolongation, slowing of heart rate, and suppression of ventricular arrhythmias. [21][22][23] The present study showed that for conversion of atrial fibrillation, plasma concentrations of desethylamiodarone were more important than those of the parent compound. This is in agreement with previous studies 24 and is possibly related to a high myocardium/plasma concentration ratio in the case of desethylamiodarone.…”
Section: Discussionmentioning
confidence: 52%